Management of bleeding and invasive procedures in patients treated with anti–factor XI(a) anticoagulants: proposals from the French Working Group on Perioperative Haemostasis and French Society of Thrombosis and Haemostasis - Anne Godier; Dominique Lasne; Anne–Céline Martin; Gilles Pernod; Pierre Albaladejo; Emmanuel De Maistre; Pierre Fontana; Thomas Lecompte; Grégoire Le Gal; Jerrold H. Levy; Mikael Mazighi; François Mullier; et al. (Research and Practice in Thrombosis and Haemostasis)
Background: Several anti-FXI(a) agents with distinct mechanisms of action and pharmacological properties are currently under clinical development. While these anticoagulants are not yet available, there is a need to address bleeding risk management for patients already enrolled in phase III trials. These patients may face elective or unplanned invasive procedures and bleeding events in anticipation of marketing authorization.Experience from managing patients with inherited FXI deficiency, along with data from early clinical trials, suggests that the bleeding risk associated with anti-FXI(a) is likely to be low but can vary depending on the clinical situation. Anti-FXI(a) reversal options include tranexamic acid, FXI concentrates, and recombinant activated factor VII. However, these options may not always be suitable, can be expensive, and may carry a thrombotic risk. Objectives: The French Working Group on Perioperative Haemostasis (Groupe d’Intérêt en Hémostase Péri-opératoire (GIHP)) and the French Society of Thrombosis and Haemostasis (SFTH) aimed to develop proposals to manage bleeding and invasive procedures in patients treated with anticoagulants targeting Factor XI or XIa (anti-FXI(a)). Methods: Literature review and development of practical guidelines by an expert panel. Results: We propose pragmatic recommendations for optimizing safety in patients treated with anti-FXI(a), considering bleeding and thrombosis risks, the drug’s mechanism of action, and available reversal options. Conclusion: These proposals will be re-evaluated as more data becomes available. The implementation of a registry for managing anti-FXI(a) anticoagulants in patients undergoing invasive procedures or experiencing bleeding complications is needed.